Averaged Turnpike Property for Differential Equations with Random Constant Coefficients - Zamorano-Aliaga, S (American Institute of Mathematical Sciences, 2023)
This paper studies the integral turnpike and turnpike in average for a class of random ordinary differential equations. We prove that, under suitable assumptions on the matrices that define the system, the optimal solutions for an optimal distributed control tracking problem remain, in an averaged sense, sufficiently close to the associated random stationary optimal solution for the majority of the time horizon. © 2023, American Institute of Mathematical Sciences. All rights reserved.